MOTIVE AND OBSTACLES IN MAKING A DECISION AS EARLY ADOPTERS OF PSAK NO. 71 FOR IMPAIRMENT PROVISION OF LOANS (STUDY CASE IN INDONESIA BANKING INDUSTRY) - Arya P. Rizal; Elvia R. Shauki (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2018)
IFRS 9 has converged into PSAK No. 71 and became effective on January 1, 2020 where early implementation is permitted. Changing in accounting standards might have caused controversy. However, there are bank in Indonesia had implemented before PSAK No. 71 effectived (early adopters). This study aims to determine the motive of early adopters of PSAK No.71, the obstacles they faced and the impact especially through loan impairment. By using study case method in Indonesia banking industry and then collect data using semi structured interviews and content analysis. DiMaggio and Powell (1983) explained that institutional theory emphasizes institutional patterns formed because the influence of policy from inside and outside the company (symbolic carriers). Therefore, the motive behind the institutions and actors (material carriers) decision to become early adopters will be revealed. In this case, we found that early adopters are mostly the bank with ownership as foreign bank and mixed bank (as subsidiary). Also, the primary motive of the bank when decide to early adopt are based on following their holding that mandatory to implement IFRS 9. This could create a good external reporting because the accounting standard between holding company and its branch or subsidiary will be similar.Keywords: Banking, Financial Instrument, Early Adopters, Institutional Theory, PSAK No. 71